Nin̲aivu alaikaḷ: tan̲ varalār̲u - Cuntaravaṭivēlu, Ne. Tu. (Vān̲ati, 1983)
Reminiscences of an educationist, social activist, and administrator from Tamil Nadu.
Title on t.p. verso: Ninaivu alaigal.
In Tamil.
Reminiscences of an educationist, social activist, and administrator from Tamil Nadu.
Keywords: Educators / India / Tamil Nadu / Biography.; Tamil Nadu (India) / Biography.